2023
DOI: 10.1002/batt.202200519
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Influence of Li+‐cation and TFSI‐anion in Poly(ionic liquid) Binders for Lithium‐Metal Batteries

Abstract: Ion transport in composite electrodes plays a key role in the electrochemical performance of lithium‐metal batteries (LMBs), particularly at high current densities, and hence, some works have suggested the use of ionic conducting polymers as binders. Herein, in order to assess the importance of the type of ion conduction in binders, two poly(ionic liquid) polymers were analyzed as binders in LiFePO4 (LFP) cathodes: poly(lithium 1‐[3‐(methacryloyloxy)propylsulfonyl]‐1‐(trifluoromethane sulfonyl) imide) (PMTFSI−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Furthermore, the sulfonate groups can be acting as lithium carriers during the charge and discharge of the battery. Therefore, by having a higher number of sulfonate groups in the structure, the lithium mobility may be boosted through ionic pathways . In addition, the larger number of sulfonate groups present in the 3SO 3 – Carr binder may contribute to the protection of the NMC811 particles against water, achieving a more stable cycling than the 1SO 3 – Carr and 2SO 3 – Carr .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the sulfonate groups can be acting as lithium carriers during the charge and discharge of the battery. Therefore, by having a higher number of sulfonate groups in the structure, the lithium mobility may be boosted through ionic pathways . In addition, the larger number of sulfonate groups present in the 3SO 3 – Carr binder may contribute to the protection of the NMC811 particles against water, achieving a more stable cycling than the 1SO 3 – Carr and 2SO 3 – Carr .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, by having a higher number of sulfonate groups in the structure, the lithium mobility may be boosted through ionic pathways. 29 In addition, the larger number of sulfonate groups present in the 3SO 3 – Carr binder may contribute to the protection of the NMC811 particles against water, achieving a more stable cycling than the 1SO 3 – Carr and 2SO 3 – Carr . This effect could be similar to the one observed by Heidbüchel et al 30 that have recently reported the positive impact of the addition of Li 2 SO 4 during the aqueous processing of NMC811 cathodes since a protective coating around the active material was observed by XPS measurements.…”
Section: Resultsmentioning
confidence: 99%
“…However, PVDF has a high fluorine content and requires the usage of the toxic and expensive organic solvent N -methyl-2-pyrrolidone (NMP) for the electrode processing and elevated temperatures for the drying step, making the cathode manufacturing process environmentally unfriendly. As an alternative to PVDF, low-fluorine-content poly­(ionic liquids) or anionic single-ion lithium conducting polymers are demonstrating enhanced cycling stability and capacity values in Li–air and solid-state batteries. As a recent example, pyrrolidinium-based poly­(ionic liquid)­s were reported as cathode binders in NMC cathodes which showed improved capacity values, rate performance, and cycling stability, In particular, PDADMA–CFSO showed a cell capacity increase of 26% at 5 C when compared to PVDF.…”
Section: Polymers As Binders Of Electrodesmentioning
confidence: 99%
“…[14,15] An interesting approach to binder formulations is the use of poly (ionic liquids)s, which contain ionic moieties in the polymer structure and, if chosen carefully, may improve the lithium diffusion and the long-term stability. [16][17][18][19][20][21][22] This subclass of polyelectrolytes have aroused interest as binder components given the possibility of improving the ionic conduction pathways within the electrode, the possibility of forming strong bonds between the active and conductive material, [23] and the flexibility provided by the polymer backbone. [24] One of the most studied poly(ionic liquid)s in energy storage applications is based on poly(diallyldimethylammonium) (PDADMA) with different counteranions.…”
Section: Introductionmentioning
confidence: 99%